The Chronic Detrimental Impact of Interruptions in a Simulated Submarine Track Management Task. (December 2015) - Loft, Shayne; Sadler, Andreas; Braithwaite, Janelle; Huf, Samuel
Objective: The objective of this article is to examine the extent to which interruptions negatively impact situation awareness and long-term performance in a submarine track management task where pre- and postinterruption display scenes remained essentially identical. Background: Interruptions in command and control task environments can degrade performance well beyond the first postinterruption action typically measured for sequential static tasks, because individuals need to recover their situation awareness for multiple unfolding display events. Participants in the current study returned to an unchanged display scene following interruption and therefore could be more immune to such long-term performance deficits. Method: The task required participants to monitor a display to detect contact heading changes and to make enemy engagement decisions. Situation awareness (Situation Present Assessment Method) and subjective workload (NASA–Task Load Index) were measured. The interruption replaced the display for 20 s with a blank screen, during which participants completed a classification task. Results: Situation awareness after returning from interruption was degraded. Participants were slower to make correct engagement decisions and slower and less accurate in detecting heading changes, despite these task decisions being made at least 40 s following the interruption. Conclusion: Interruptions negatively impacted situation awareness and long-term performance because participants needed to redetermine the location and spatial relationship between the displayed contacts when returning from interruption, either because their situation awareness for the preinterruption scene decayed or because they did not encode the preinterruption scene. Application: Interruption in work contexts such as submarines is unavoidable, and further understanding of how operators are affected is required to improve work design and training.